ANALISIS KUALITAS AIR DENGAN PARAMETER TSS, BOD, DETERJEN DAN FOSFAT (PO4) PADA SUNGAI WANGGU KOTA KENDARI - Hema Hema; Moch. Assiddieq; Wa Ndibale; Ilham Ilham; Dwiprayogo Wibowo (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Wanggu River is the largest river in Kendari City – Southeast Sulawesi (Sultra), whose condition is very poor because it is a final place for disposal of household and industrial wastewater. It will be impacted by decreasing water quality and silting sedimentation. In this study, it is important to analyze the water quality of the Wanggu River with several physical and chemical parameters analysis such as the determination of total suspended solids (TSS), biochemical oxygen demand (BOD), the content of phosphate (PO4), and detergent pollutants which are determined based on location sampling such as upstream, middle, and downstream. Based on these results showed that the TSS and PO4 contents from the upstream, middle, and downstream points had increased in concentration, while the BOD and detergent contents have decreased in the downstream area. However, this condition shows that the Wanggu River is still categorized as Class II within the normal threshold. These results are expected to become a reference for the government and society in improving wastewater management and increasing knowledge in managing river water quality.